Plasma homocysteine concentrations and serum lipid profile as atherosclerotic risk factors in subclinical hypothyroidism - Turhan, Serpil (Ann Saudi Med, 2008)
BACKGROUND AND OBJECTIVES: Because subclinical thyroid dysfunction may be a risk factor for cardiovascular disease, we evaluated the atherosclerosis tendency in subclinical hypothyroid (SCH) patients. PATIENTS AND METHODS: Fifty-three subclinical hypothyroid patients (serum thyrotropin [TSH] concentrations >4.12 mU/L) were compared with a control group of 50 euthyroid subjects whose age, sex and body mass indices were similar to the patient group. We tested whether serum TSH concentrations were correlated with plasma total homocysteine concentration (tHcy), low-density lipoprotein cholesterol (LDL-C), very low-density lipoprotein cholesterol (VLDL-C), high-density lipoprotein cholesterol (HDL-C), total cholesterol (TC) and triglycerides (TG). RESULTS: There was a significant statistical difference between the patient and control groups for normal free T4 (1.02±0.17 vs. 0.86±0.13, P<.001), TSH (1.64±1.02 vs. 6.62±2.61, P<.001), TC (185±39 vs. 206±42, P=.01), TG (103±54 vs. 132±85, P=.04), LDL-C (114±33 vs. 127±36, P=.04), and TC/HDL-C (3.81±106 vs. 4.19±1.02, P=.04), respectively. No statistically significant difference was found between the two groups for HDL-C, VLDL-C, LDL-C/HDL-C, and tHcy. Serum TSH was significantly correlated with plasma tHcy (r=0.55; P=.001), TC (r=0.52; P=.001), LDL-C (r=0.49; P=.001), TC/HDL-C (r=0.38; P=.002) and LDL-C/HDL-C (r=0.36; P=.004) across all participants. CONCLUSION: Our study suggests that the atherogenicity of SCH is not mediated by hyperhomocysteinemia. Associated hyperlipidemia may explain the observed increased risk of coronary artery disease in patients with SCH.